The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.11622/smedj.2013064
|View full text |Cite
|
Sign up to set email alerts
|

Gantzer muscles and their applied aspects: an exceptional finding

Abstract: Anatomical variations are typically more common in the extensor compartment of the forearm, but uncommon in the flexor compartment. The presence of such anatomical anomalies is not usually noticed until the normal functions of an individual become hindered, or when these anomalies become a surgical problem. During routine dissection curriculum, we encountered a rare finding of bilateral Gantzer muscles in a cadaver. We describe the relationship between the Gantzer muscle and anterior interosseous nerve syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Saxena et al 17 reported that during routine dissection they found the presence of Gantzer muscle bilaterally in one corpse, citing that this muscle was a very rare finding; this statement is in disagreement with the aforementioned authors, since almost all of them found the presence of muscle in more than 50% of the dissected limbs.…”
Section: Discussionmentioning
confidence: 87%
“…Saxena et al 17 reported that during routine dissection they found the presence of Gantzer muscle bilaterally in one corpse, citing that this muscle was a very rare finding; this statement is in disagreement with the aforementioned authors, since almost all of them found the presence of muscle in more than 50% of the dissected limbs.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, symptom reproduction during resisted contraction of the flexor superficialis is suggestive of an entrapment beneath the arch of the flexor digitorum superficialis [7]. Finally, a few cases of nerve entrapment syndrome are described without any anatomic constraints nor specific location [9]. …”
Section: Pronator Syndromementioning
confidence: 99%